Characterization of the complete chloroplast genome of the ornamental plant Osmanthus cooperi. Issue 2 (3rd July 2019) - Wang, Xiaofei; Cai, Fuyue; Zhang, Cheng; Zhang, Min; Li, Yongfu; Duan, Yifan
Abstract: Osmanthus cooperi is an evergreen ornamental plant belonging to the olive family. In this study, its complete chloroplast genome was assembled from the whole genome Illumina sequencing data. The circular genome is 155, 262 bp long, and comprises a pair of inverted repeat regions (IRs, 25, 685 bp each), a large single-copy region (LSC, 86, 525 bp), and a small single-copy region (SSC, 17, 367 bp). It encodes 132 genes, including 8 rRNA genes, 36 tRNAs genes, and 88 protein-coding genes. The GC content of O. cooperi cp genome is 37.8%. Phylogenetic analysis indicates that O. cooperi is close to O. fragrans in Oleaceae.